THE EFFECT OF GOAL SETTING TRAINING ON WORK EFFECTIVENESS OF ASN IN SURABAYA - Anugrahani Sabillia Noor Pratama; Fendy Suhariadi (SOSIOEDUKASI, 2025)
Organizational development is a structured approach oriented towards systematic change to improve organizational effectiveness. This study was conducted at BKPSDM Surabaya City Government, focusing on diagnosing problems and designing interventions based on goal setting to improve the alignment of organizational and individual goals. This study uses Cummings & Worley's (2015) organizational development model, which consists of five main stages: entering and contracting, diagnosing, planning and implementing change, evaluating, and institutionalizing. The diagnosis process was conducted using the Organizational Diagnosis Questionnaire (ODQ) developed from Weisbord's Six Box Model (1976), including six main components: purpose, structure, leadership, relationships, rewards, and helpful mechanisms. The diagnosis results showed that the purpose component had the lowest score, indicating employees' weak understanding of the organization's vision, mission, and strategic goals. Based on these findings, a goal setting intervention was designed collaboratively to increase employee engagement, role clarity, and synchronization between personal and organizational goals. The intervention design included group goal setting, meetings between superiors and subordinates, creation of individual action plans, and periodic evaluation of achievements. The findings suggest that a participatory OD approach can provide an effective framework for building a more adaptive, transparent, and long-term results-oriented goal-setting system in public sector organizations